DEVELOPMENT OF EATING ABILITY IN MODERATE INTELECTUALLY DISABLED CHILDREN AT WISMA GONDOSULI 8 BHAKTI LUHUR ORPHANAGE, MALANG - Gardiana Karya (Journal of ICSAR, 2022)
In everyday life, humans need food, therefore everyone must have eating skills, including children with moderate intellectual disability. This research is focused on children with moderate intellectual disability with the inability to eat independently . This study aims to describe: the ability to develop self-feeding in children with moderate intellectual disability. This research is a qualitative descriptive study. The research subjects are two intellectually disabled children in grade 2 SDLB who live in  Bhakti Luhur Orphanage, Malang. Data collection was carried out by observation (participant) because the researcher lived with the children and the data was documented. The steps of data analysis used descriptive qualitative analysis, namely presenting data in narrative form. The results showed that the ability to develop self-feeding in moderate intellectual disabled  children was still in the moderate category because it still needed further assistance and training. Suggestions for companions to remain patient and diligent in training the abilities of moderate intellectual disabled children to train them repeatedly in the same way until children have eating skills.